2008
DOI: 10.1007/s00281-008-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms in the pathogenesis of diabetic retinopathy

Abstract: There is an accumulating body of evidence that immunological mechanisms play a prominent role in the pathogenesis of diabetic retinopathy (DR), which is characterized by many features typical of inflammation. The upregulation of cytokines and other inflammatory mediators leading to persistent low-grade inflammation and an influx of leukocytes, is believed to contribute actively to DR-associated damage to the retinal vasculature and retinal neovascularization. This review will describe preclinical and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(203 citation statements)
references
References 123 publications
4
196
0
3
Order By: Relevance
“…The cytokines and mediators are said to contribute actively to DR-associated damage to the retinal vasculature and neovascularization. 23 RANTES produced by inflammatory cells, retinal endothelial cells, and pigment epithelial cells 24 is a member of the chemokine family. Meleth et al 7 showed that RANTES levels largely increased in subjects with severe NPDR versus less severe NPDR (Po0.001), but RANTES levels unexpectedly decreased in subjects with less severe NPDR versus normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines and mediators are said to contribute actively to DR-associated damage to the retinal vasculature and neovascularization. 23 RANTES produced by inflammatory cells, retinal endothelial cells, and pigment epithelial cells 24 is a member of the chemokine family. Meleth et al 7 showed that RANTES levels largely increased in subjects with severe NPDR versus less severe NPDR (Po0.001), but RANTES levels unexpectedly decreased in subjects with less severe NPDR versus normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in experimental diabetic models, the early signs of diabetic retinopathy include vascular leakage, the mechanism by which hyperglycemiainduced vascular leakage is believed to be an inflammatory reaction between ROS and cell adhesion molecules such as CD18 and ICAM-1. This reaction induces breakdown of blood-retinal barrier and causes tissue ischemia, resulting in neuronal or retinal cell death [77]. Result of a recent research documented an important proinflammatory role of MMPs including MMP-2 and -9 in retina of diabetic animal [69,78].…”
Section: Mmps and Inflammationmentioning
confidence: 99%
“…Clinical studies have established that VEGF concentrations are elevated in eyes with DME (Funatsu et al, 2003;Funatsu et al, 2005), and preclinical studies have demonstrated that VEGF levels increased after its onset in a manner temporally correlated with the breakdown of the blood-retinal barrier (Qaum et al, 2001). Several mechanisms are believed to underlie these actions; in addition to the direct action of VEGF on the permeability of intact blood vessels, it also promotes an influx of inflammatory cells that produces endothelial cell apoptosis in the retinal vasculature (Adamis & Berman, 2008).…”
Section: Anti-vascular Endothelial Growth Factor (Anti-vegf) Injectionmentioning
confidence: 99%